Clinical profile of patients assisted in a physical therapy outpatient service in oncology of Sao Paulo city - Mutti Tacani, Pascale; Tamy Kasawara, Karina; Tacani, Rogério Eduardo; Peres Machado, Aline Fernanda; Montezello, Débora; Guedes Sampaio Góes, João Carlos (O Mundo da Saúde, 2014)
Advances in cancer treatment has been favoring higher survival rates, increasing demand of rehabilitation of cancer patients, being physical therapy one of the areas in a higher growth. However, this population has very different profiles, demands and realities, requiring the knowledge of its features to better develop action strategies and conducts in the area of physical therapy in oncology. The objective of this study was to identify the clinical profile of patients assisted in a physical therapy outpatient in Oncology. One hundred five medical records were analyzed for demographic and clinical data collection in a outpatient physiotherapy service of Sao Paulo city, from August 2008 to July 2010, being 11(10.5%) excluded. Statistical analysis was performed using the test for equality of two proportions to evaluate the relative distribution of variables, which were compared using the Mann-Whitney test. Among those 94 medical records, 63.8% (n = 60) were female (p < 0.001), with a mean age of 56.3 ± 13.3 years and they had a BMI of 27.09 ± 5.88 kg/m². The most prevalent medical diagnosis was breast cancer in 44.4% (n = 44; p < 0.05). Most patients were between the second and the fifth year (33%; n = 31) of disease evolution. Surgery was the most common treatment (94.7%; n = 89; p < 0.001). The most frequent physiotherapeutic diagnosis included vascular and lymphatic dysfunctions (87.2%; n = 82; p < 0.001) with complaints of pain (55.3%; n = 52) and swelling (51.1%; n = 48; p = 0.559). It was concluded that the clinical profile of patients was characterized by woman, over 50 years old, overweight in late postoperative breast cancer, exhibiting lymphedema and pain in the limbs.